Dukungan Regulasi dalam Pembangunan Kelautan dan Perikanan di Aceh Besar - Muhammad Insa Ansari (Universitas Syiah Kuala, 2014)
Maritime and fishery development provides important meaning for the development in Aceh Besar. In final report of Head and Vice Head period 2007-2012 has been mentioned that the development fishery providing big opportunity in PDRB of the region is decreased. It results from many infrastructures are destroyed due to the tsunami disaster. Law might play a role in economic development. In this case, it creates stability, predictability, and fairness. Based on that view on the regulation both Qanun Aceh Besar and the Regulation of Head District issued is based on maritime and fishery sectors. At the regulation level, during 2007 to 2012, there are four regulations relating to the development of fishery and maritime sectors. Regulation Support in Maritime and Fishery Development in Aceh Besar